2008
DOI: 10.1111/j.1447-0594.2008.00452.x
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life of the community‐based patients with mild cognitive impairment

Abstract: The MCI patients had poorer psychological QOL than normal subjects. Low education, poor financial status, living alone and depressive symptoms had an influence on the quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
49
2
4

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(67 citation statements)
references
References 14 publications
7
49
2
4
Order By: Relevance
“…The other study used the Alzheimer's Disease related QoL (Rabins, Kasper, Kleinman, Black, & Patrick, 1999), which reflects caregiver judgments about the patient's social interaction, awareness of self, feelings and mood, enjoyment of activities, and response to surroundings; and since it tackles rather basic behaviors of the patient, it may not be sensitive to early phases of cognitive decline. Still another study found in patients with MCI differences in one domain, psychological QoL, but not in other domains or in total score of the self-reported World Health Organization QoL scale (Muangpaisan et al, 2008).…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…The other study used the Alzheimer's Disease related QoL (Rabins, Kasper, Kleinman, Black, & Patrick, 1999), which reflects caregiver judgments about the patient's social interaction, awareness of self, feelings and mood, enjoyment of activities, and response to surroundings; and since it tackles rather basic behaviors of the patient, it may not be sensitive to early phases of cognitive decline. Still another study found in patients with MCI differences in one domain, psychological QoL, but not in other domains or in total score of the self-reported World Health Organization QoL scale (Muangpaisan et al, 2008).…”
mentioning
confidence: 89%
“…It is controversial whether QoL is already disturbed in more initial phases of cognitive decline, like Mild Cognitive Impairment (MCI), a clinical entity now accepted in both clinical practice and research that entails a high risk of progression to dementia. Some researchers found that QoL is not affected in MCI patients (Missotten et al, 2008;Ready et al, 2004) while other detected that some aspects of QoL are altered (Muangpaisan, Assantachai, Intalapaporn, & Pisansalakij, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…In general, persons with MCI report more difficulties than healthy elderly individuals with engaging in social conversation, telephone use, finding belongings, grocery shopping, driving, and medication management (Aretouli & Brandt, 2009; Muangpaisan, Assantachai, Intalapaporn, & Pisansalakij, 2008; Kim et al, 2009; Peres et al, 2006; Ryu, Ha, Park, Yu, & Livingston, 2010; Schmitter-Edgecombe, Woo, & Greeley, 2009; Wadley et al, 2008). Psychological well-being has been examined in four studies of people with MCI and has included measures of life satisfaction, mastery, affect, and social interaction (Ready, Ott, & Grace, 2004).…”
Section: Living With MCImentioning
confidence: 99%
“…Muangpaisan et al 32 empregaram o mesmo questionário de QV e observaram que os idosos tailandeses da comunidade, com deficiência cognitiva leve, apresentaram piores escores apenas no domínio psicológico de QV quando comparados a idosos sem essa afecção. Os piores escores na EDG dos idosos com a deficiência cognitiva leve se associaram aos piores escores nos domínios físico e psicológico do WHOQOL-Bref, assim como ser mais velho (70 e mais anos) correlacionou-se ao domínio físico e viver só, ao domínio relações sociais.…”
Section: Materials E Métodounclassified
“…Os piores escores na EDG dos idosos com a deficiência cognitiva leve se associaram aos piores escores nos domínios físico e psicológico do WHOQOL-Bref, assim como ser mais velho (70 e mais anos) correlacionou-se ao domínio físico e viver só, ao domínio relações sociais. 32 Dentre as doenças mais frequentemente encontradas, estão as afecções musculoesqueléticas. Notou-se, neste estudo, que os idosos com afecções musculoesqueléticas apresentaram prejuízo na QV em todos os domínios avaliados pelo WHOQOL-Bref, provavelmente porque elas podem impedir ou limitar as atividades dos idosos, dificultando o sair de casa para consultas médicas ou atividades de lazer.…”
Section: Materials E Métodounclassified